Adipocyte Na, K-ATPase Signaling Attenuates Experimental Uremic Cardiomyopathy: Role of Adipocyte in Uremic Cardiomyopathy - Sodhi, Komal; Wang, Xiaoliang; Chaudhary, Muhammad A.; Lakhani, Hari Vishal; Zehra, Mishghan; Nawab, Athar; Cottrill, Cameron L.; Bai, Fang; Liu, Jiang; Sanabria, Juan R.; Xie, Zijian; Shapiro, Joseph I. (Cellular and Molecular Biology, 2023)
Oxidative stress has been shown to cause an alteration of intracellular signaling in adipocytes that may lead to various comorbidities of obesity and cardiovascular complications. Evidence suggests that dysregulation of Na, K-ATPase signaling can contribute to systemic inflammation and redox signaling that leads to various metabolic disturbances. Hence the present study aims to explore the specific role of adipocyte Na, K-ATPase signaling in the amelioration of pathophysiological alterations of experimental uremic cardiomyopathy. Experimental uremic cardiomyopathy was induced by partial nephrectomy (PNx), and adipocyte-specific expression of NaKtide, a peptide that inhibits Na, K-ATPase signaling, was achieved using a lentivirus construct with NaKtide expression driven by an adiponectin promoter. Cardiomyopathy and anemia induced in partial nephrectomy mice were accompanied by an altered molecular phenotype of adipocytes, increased systemic inflammatory cytokines and oxidant stress within 4 weeks. These changes were significantly worsened by the addition of a Western diet (enriched in fat and fructose contents) but were prevented with specific expression of NaKtide in adipocytes. The skeletal muscle-specific expression of NaKtide did not ameliorate the disease phenotype. Adipocyte dysfunction and uremic cardiomyopathy developed in PNx mice, both were significantly ameliorated by the adipocyte-specific expression of NaKtide. These findings suggest that oxidative milieu in the adipocyte has a pivotal role in the development and progression of uremic cardiomyopathy in mice subjected to partial nephrectomy. If confirmed in humans, this may be a lead for future research to explore novel therapeutic targets in chronic renal failure.